Wood hemicelluloses exert distinct biomechanical contributions to cellulose fibrillar networks - Jennie Berglund (Nature Portfolio, 2020)
Hemicelluloses are an essential constituent of plant cell walls, but the individual biomechanical roles remain elusive. Here the authors report on the interaction of wood hemicellulose with bacterial cellulose during deposition and explore the resultant fibrillar architecture and mechanical properties.